Aesthetics and politics in the ayllu school of Warisata: An approach to the expressionism of Mario Alejandro Illanes - Salazar de la Torre, Cecilia (2006)
Warisatt Wawan Chamapa -"with the efforts of the children of Warisata"- and Takke Jakken utapa -"everyone's house", in the Aymara language, are the phrases -on the front of the main structure- with which the School-Ayllu of Warisata -the first normal school for rural teachers in Bolivia- welcomes its visitors.